Dampak Komunikasi terhadap Efektivitas Organisasi pada PT. Pertamina (Persero) Retail Kota Medan - Chairunisa, Nia (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2024)
Given the communication concerning organizational effectiveness, a company that wants to continue to grow must make various efforts to realize what the company wants, therefore it is necessary to establish effective communication. In realizing an effective company is not an easy problem, the company will encounter various challenges. Solving these challenges depends on how the company is able to provide the right solutions to the problems encountered.The results of this study indicate that upward communication has a positive and significant influence on organizational effectiveness at PT Pertamina (Persero) Retail Kota Medan. Horizontal communication has a positive and significant influence on organizational effectiveness at PT Pertamina (Persero) Retail Medan City. In the simultaneous test or simultaneous test, the ability of independent variables (upward communication and horizontal communication) has a simultaneous effect on the dependent variable, namely the organizational effectiveness of PT Pertamina (Persero) Retail Medan City. This study aims to determine the effect of upward communication and horizontal communication on organizational effectiveness at PT Pertamina (Persero) Retail Kota Medan. The population in this study were all employees who worked at PT Pertamina (Persero) Retail Medan City as many as 120 people, all members of the population were used as research samples as many as 120 people.